2020
DOI: 10.1128/aem.01319-20
|View full text |Cite
|
Sign up to set email alerts
|

Editing of the Proteolytic System of Lactococcus lactis Increases Its Bioactive Potential

Chenxi Huang,
Jan Kok

Abstract: Large-scale mass spectrometry-based peptidomics for bioactive peptide discovery is relatively unexplored because of challenges in intracellular peptide extraction and small peptide identification. Here we present an analytical pipeline for large-scale intracellular peptidomics of Lactococcus lactis. It entails an optimized sample preparation protocol for L. lactis, used as an “enzyme complex” to digest β-casein, an extraction method for its intracellular peptidome, and a peptidomics data analysis and visualiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
(36 reference statements)
0
6
0
Order By: Relevance
“… Lactococcus lactis and Enterococcus faecalis were found to be adequate candidates. Both species possess a very efficient proteolytic system and can modify sensorial profiles in cheeses and other fermented dairy products ( 16 , 17 ). The E. faecalis proteolytic system was even shown to be responsible for a decrease of allergenicity of bovine milk proteins ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“… Lactococcus lactis and Enterococcus faecalis were found to be adequate candidates. Both species possess a very efficient proteolytic system and can modify sensorial profiles in cheeses and other fermented dairy products ( 16 , 17 ). The E. faecalis proteolytic system was even shown to be responsible for a decrease of allergenicity of bovine milk proteins ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Milk fermentation processes executed by LAB are preferable ways to generate peptides due to the GRAS status of these organisms. The proteolytic system of L. lactis has been comprehensively analyzed with respect to the genes and enzymes involved, as well as their regulation [261][262][263][264]. It was reported that during bovine milk fermentation with L. lactis, numerous casein-derived bioactive peptides can be generated, most of which have angiotensin-converting enzyme (ACE) inhibitory activity, leading to an antihypertensive effect [36,260,265].…”
Section: Bioactive Peptidesmentioning
confidence: 99%
“…The ability to preferentially cleave these regions could confer a selective growth advantage to L. helveticus. Huang and Kok [30 ] combined deletion of pep genes and nanoLC-MS/MS to identify novel bioactive peptides released from b-casein by Lactococcus lactis pep mutants.…”
Section: Dairy Fermented Foodmentioning
confidence: 99%